Pemberdayaan Masyarakat melalui Alokasi Dana Desa dalam Upaya Meningkatkan Kesejahteraan Masyarakat - Elly Lestari; Dadang Kuswana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this study was to find out the use of village fund allocation in supporting community empowerment, community empowerment strategies and knowing the results of community empowerment through Alokasi Dana Desa in an effort to improve community welfare. This research departs from the framework of thinking that empowerment is a process and purpose in improving people’s walfare. Based of the theory according to Edi Suharto the empowerment process through several stages including determining funding sources, funding sources and empowerment is an inseparable thing. The research method used is a descriptive method with a qualitative appoarch as a problem solving procedure that is examined by discrimbing the actual state of the object of research. While the findings say that community empowerment through Alokasi Dana Desa can improve people’s welfare because the source of funding and empowerment are inseparable because something cannot be empowerment without funds. Therefore, this funding source becomes an important part of the empowerment process.